Evaluasi Pemuktahiran Data Pemilih dan Penyusunan Daftar Pemilih dalam Pemilihan Umum Tahun 2024 di Kota Bitung - Palenewen, Jovano Deivid Oleyver; Sendouw, Yurnie; Pangemanan, Johnly Roycke (Journal Ilmu Sosial, Politik dan Pemerintahan, 2025)
Elections are an instrument to build a democratic civilisation in Indonesia. Its implementation is expected to answer the will of the people. The Election in 2024 may run smoothly and successfully. Although there are still some issues that need to be improved, including the accommodations of people's political rights in the voters list. This paper is the result of research that explains the evaluation of general elections in the stages of updating voter data and preparing voter lists in Bitung City. The research method used is descriptive qualitative. Data taken both primary and secondary data that supports. Informants addressed to the Election Organiser in Bitung City, Bitung City Government and the Community